Analisis Dampak Penggunaan Situs Web ChatGPT dalam Proses Pembelajaran Biologi Siswa SMA Negeri 1 Torue - I Ketut Didiana; Bustamin; Gamar Binti Non Shamdas; Musdalifah Nurdin; Mohhamad Sabran; Lilies (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe the impact of using the ChatGPT website in the learning process of Biology students at SMA Negeri 1 Torue. This study uses a qualitative method with a descriptive approach. The subjects in this study were students from SMA Negeri 1 Torue XI and XII, with the number of subjects taken as 10% of the total student population, with 32 students in grade XI and 30 students in grade XII. Data collection techniques involved using a questionnaire filled out by the students, with evaluations using a Likert scale. Observations at SMAN 1 Torue revealed that students have extensively used ChatGPT in the learning process during discussions, and the use of ChatGPT in the biology learning process has both positive and negative impacts. The results of this study indicate the impact of ChatGPT use on the cognitive aspect with an average total percentage of 59%, on the affective aspect with an average total percentage of 69%, and on the psychomotor aspect with an average total percentage of 41%. It can be concluded that there is an impact of using the ChatGPT website in the learning process of Biology students at SMA Negeri 1 Torue.